Comparison of configurations for a compact regenerative evaporative cooler - Lee, Joohyun; Choi, BongSu; Lee, Dae-Young (PERGAMON-ELSEVIER SCIENCE LTD, 2013)
The regenerative evaporative cooler (REC) cools a stream of air using evaporative cooling effect without an increase in the humidity ratio. In the regenerative evaporative cooler, the air can be cooled down to a temperature lower than its inlet wet bulb temperature. Besides the cooling performance, for practical application of the REC, the compactness of the system is also a very important factor to be considered. In this study, three different configurations, i.e., the flat plate type, the corrugated plate type, and the finned channel type are investigated and compared for the most compact configuration. The optimal structure of each configuration is obtained individually to minimize the volume for a given effectiveness within a limit of the pressure drop. Comparing the three optimal structures, the finned channel type is found to give the most compact structure among the considered configurations. The volume of the regenerative evaporative cooler can be reduced to 1/8 by adopting the finned channel type as compared to that of a flat plate type. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: SURFACE HEAT-EXCHANGERS; POROUS-MEDIA; COUNTER-FLOW; PERFORMANCE